Pelatihan Kepemanduan di Desa Wisata Donokerto - Yudi Setiaji (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Guidance Training in Donokerto Tourism Village. Donokerto village is one of the pioneering tourist villages that has good potential in terms of the diversity of tourist attractions. As a Pioneer tourism village, the village of Donokerto requires qualified human resources for tourism services, especially as a tour guide. Therefore, the AMPTA Yogyakarta Tourism School in collaboration with PUM Netherlands Senior Experts held a community service with the theme